Inaugural Lecture : Congenital limb deformity : replace, repair or remove - Ahmad Hata, Rasit (Universiti Malaysia Sarawak (UNIMAS), 2016)
Introduction : The word congenital refers to a condition existing since birth. It is important to distinguish the concepts of congenital and genetic, the two terms that are often confusing to many people. Congenital abnormality indicates that the feature is present at birth and can be caused by genetic or non-genetic disorder. Hence `congenital deformity', also known as the birth defect, is a condition that exists at or before birth regardless of the causes, while the term `congenital anomalies' specifically indicates the structural deformities and normally involved structural defects in a developing fetus. Congenital deformities occur in approximately 3% of live newborns. The incidence of congenital deformity causing deaths is almost 632,000 cases in 2013. The type of deformities that most contributed to the death tolls is congenital heart defect, followed by neural tube defects (GBD, 2014). Congenital limb deformities occur in approximately 6 per 10,000 live births, with the upper limb affected more as compared to the lower limb. The congenital limb deformities usually associated with other congenital deformities such as cardiovascular, nervous or genitourinary system (Canfield, 2006).